Health care providers knowledge, attitudes and perceived barriers towards emergency contraception in a sub-Himalayan state of India - Gupta, Rajiv Kumar; Langer, Bhavna; Singh, Parveen; Kumari, Rashmi; Akhtar, Najma; Gupta, Riya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency Contraception (EC) is a method of contraception used within 72 hours of unprotected sex to prevent unwanted pregnancy. More than ten years since its use, a study was conducted among health care providers to assess their knowledge, attitudes and perceived barriers towards EC. Methods: The current cross-sectional study was conducted among the health care providers (HCPs) in all the health institutions of Jammu city, one of which included a tertiary care teaching hospital. The HCPs for the purpose of the current study included Medical Officers (MOs), Lady Health Visitors/ Staff Nurses (LHV/ SNs) and pharmacists. A 24 item pre-tested questionnaire was administered to the respondents to gather the relevant information. Results: MOs and LHV/SNs were found to have better knowledge than the pharmacists. Higher proportion of LHV/SNs and pharmacists were willing to learn more about EC (p<0.05). About two-third of MOs and LHV/SNs agreed about shortage of time during clinic schedule to counsel the users about EC (p<0.05). Conclusions: Gaps in the knowledge of the respondents need to be taken care of with continuing in-service trainings along with behaviour change communication. Role of pharmacists as health care provider especially in the context of family welfare services needs to be reassessed.